The New Molecular Dynamics Approach to Study Radiation Processes - Mykytenko, N. (Physics and Chemistry of Solid State, 2015)
A new modification of the classic method of molecular dynamics is proposed. Method allows clarifying the input of different intervals of the stationary energy spectrum of the incident particles to the final radiation effect. A shock function is introduced that describes the transfer of the corresponding pulse to the crystal atom. The action of shock function is determined by the random function that provides the necessary frequency and the magnitude of shocks. The approach is demonstrated on the example of the ion irradiation of trihydric crystal. It was found that in certain energy intervals “heavy clusters” are formed.